UPAYA MENINGKATKAN INFRASTRUKTUR PEMBELAJARAN DAN LINGKUNGAN UNTUK BERKELANJUTAN PRAKTIK MUTU PENDIDIKAN - Maksum Utsman; Bahtiar Bahtiar; Nurul Yakin (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2022)
ABSTRACTThe current study examines the state of the learning environment and infrastructure, along with their effect on teaching and learning activities and the extent to which they are maintained. This study uses a descriptive survey design paradigm. Respondents consisted of madrasah in the Darul NW Kamal Kembang Kerang Islamic boarding school with 5 madrasa principals and 127 teachers who were randomly selected using a multi-stage sampling technique from a group of 5 madrasah in the Darul Kamal Islamic boarding school Kembang Kerang environment. Data was collected using the Learning Environment Management Questionnaire (LEMQ), Teacher Instructional Task Performance Assessment Scale (SPKTIG), and Principal Interview Guidelines (IGP). The study revealed that teachers' perceptions of the quality of learning facilities and environments ranged from 41 to 60.5%, while schools with inadequate quality ranged from 19 to 59%. This implies that quality assurance practices are at the average level in secondary schools. The results also showed that there was a significant relationship between teachers' instructional tasks and students' academic performance (r = 0.645 at p<0.05). The study concludes that schools and other stakeholders in education must effectively collaborate and contribute significantly to the development of infrastructure and learning environments, so as to create a work environment that is more conducive to the practice of ensuring sustainable high-quality education in secondary schools.Key words: Infrastructure, Learning Environment, Quality of Education